A Review on the Synthesis and Bioactivity Aspects of Beauvericin, a Fusarium Mycotoxin - Wu, Qinghua; Patocka, Jiri; Nepovimova, Eugenie; Kuca, Kamil (Frontiers in Pharmacology, 2018)
Beauvericin (BEA) is an emerging Fusarium mycotoxin that contaminates food and feed globally. BEA biosynthesis is rapidly catalyzed by BEA synthetase through a nonribosomal, thiol-templated mechanism. This mycotoxin has cytotoxicity and is capable of increasing oxidative stress to induce cell apoptosis. Recently, large evidence further shows that this mycotoxin has a variety of biological activities and is being considered a potential candidate in the medicine and pesticide researches. It is noteworthy that BEA is a potential anticancer agent since it can increase the intracellular Ca2+ levels and induces the cancer cell death through oxidative stress and apoptosis. BEA has effective antibacterial activity against both pathogenic Gram-positive and Gram-negative bacteria. Importantly, BEA exhibits an effective inhibit capacity on human immunodeficiency virus type-1 integrase. Moreover, BEA can simultaneously target drug resistance, and morphogenesis provides a promising strategy to combat life-threatening fungal infections. Thus, in this review, the synthesis and the biological activities of BEA as well as the underlying mechanisms are fully analyzed. The risk assessment of BEA in food and feed are also discussed as well. We hope this review will help to further understand the biological activities of BEA and cast some new light on drug discovery.